Standard Needle Magnetization for Ultrasound Needle Guidance: First Clinical Experiences in Fine‐Needle Aspiration Cytology of Thyroid Nodules. (12th June 2019) - Freesmeyer, Martin; Kühnel, Christian; Gühne, Falk; Seifert, Philipp
Abstract : Fine‐needle aspiration cytology using a novel ultrasound needle guidance system on the basis of standard needle magnetization was consecutively performed in 30 (15 in‐plane and 15 out‐of‐plane) suspicious thyroid nodules. Nondedicated, commercially available needles were used. The technical effectiveness and safety of the system were satisfying; system failures were observed in 2 cases. The needle tip could be (at least occasionally) visualized inside the thyroid nodule in 96%, and the subjective procedure ratings were excellent in 57%. The out‐of‐plane technique was significantly superior in both respects ( P = .021 and .027, respectively). Standard needle magnetization ultrasound needle guidance was easy to apply and cost‐effective and has the potential to improve fine‐needle aspiration cytology performance.